Ward's valley - Curnow, Bobby (Top Shelf Productions, 2018)
A grumpy gnome named Ward finds himself in a battle against trolls and humans invading his beloved valley. And though he'd rather be left alone, he'll need to team up with another troll named Marta and the other forest creatures to defend their homeland.